Challenges in circulating tumor cell detection by the CellSearch system - Andree, Kiki C.; van Dalum, Guus; Terstappen, Leon W.M.M. (Molecular oncology, 2016)
Enumeration and characterization of circulating tumor cells (CTC) hold the promise of a real time liquid biopsy. They are however present in a large background of hematopoietic cells making their isolation technically challenging. In 2004, the CellSearch system was introduced as the first and only FDA cleared method designed for the enumeration of circulating tumor cells in 7.5 mL of blood. Presence of CTC detected by CellSearch is associated with poor prognosis in metastatic carcinomas. CTC remaining in patients after the first cycles of therapy indicates a futile therapy. Here we review challenges faced during the development of the CellSearch system and the difficulties in assigning objects as CTC. The large heterogeneity of CTC and the different approaches introduced in recent years to isolate, enumerate and characterize CTC results in a large variation of the number of CTC reported urging the need for uniform definitions and at least a clear definition of what the criteria are for assigning an object as a CTC. •CTC enumeration and characterization hold the promise of a real time liquid biopsy.•Challenges for detection of rare tumor cells in blood are reviewed.•Frequent oversight is to accurately detect “rare cells” among all other events.•A uniform definition for assigning an object as a CTC is urgently needed.